Modified polyriboinosinic-polyribocytidylic acid complex: sustained interferonemia and its physiological associates in humans. - Champney, K J (1979)
Fourteen patients with severe viral illnesses were given intravenous infusions of a modified interferon inducer, polyriboinosinic-polyribocytidylic acid-poly-L-lysine complexed with carboxymethylcellulose [poly)I:C.LC)], during a phase 1 clinical trial. The first eight patients received 0.15 to 0.30 mg of poly(I:C.LC) per kg of body weight daily for 5 consecutive days, and another received two courses separated by 1 week. A second group of five patients was given single intravenous infusions of 0.10 to 0.15 mg of poly(I:C.LC) per kg. Interferon was detectable in the serum 8 to 16 h after injection. Titers ranged from 15 to 800 U/ml and varied directly with the dose of poly(I:C.LC). Interferonemias persisted for 12 to 48 h. In patients receiving 5-day courses of poly(I:C.LC), lower levels of serum interferon (0 to 160 U/ml) occurred on days 2 through 5, characteristic of a hyporesponsive state. An exception was a 69-year-old patient with disseminated varicella zoster, multiple myeloma, and renal insufficiency whose serum contained 3,150 U of interferon per ml on day 3 of 0.3 mg of poly(I:C.LC) per kg. Fever (39 to 40.5 degrees C, rectally; 13 of the 14 patients) peaked 3 to 8 h after completion of infusions. Other toxic effects included lymphopenia (10 of the 14 patients), hypotensive episodes (7 of the 14 patients), and minor elevations of serum glutamicoxalacetic transaminase and lactic dehydrogenase.